Translation and validation of food insecurity experience scale FIES - Mat Ya, Roselawati; Sidek, Suriati; Ab Rahman, Jamalludin; Sulaiman, Norhasmah; Yahya, Noor Atirah; Halimatun Saadiah; Jaafar, Nurul Hazirah; Mohd Abu Bakar, Wan Azdie (Nutrition Society of Malaysia, 2021)
Introduction: Food insecurity has a complex and multifaceted concept and definition, thus assessing it has been an ongoing challenge for researchers, health practitioners, and policy makers. Previous studies reported inconsistent findings on the prevalence and severity of food insecurity, depending on the measuring tools used. To overcome this limitation, this study aimed to translate and validate the Food Insecurity Experience Scale (FIES) for Malaysians, which has been used as a standard measurement by Food and Agriculture Organization (FAO). Methods: Two forward and backward translations involving experts in food insecurity studies and experts in language were done, as well as the pre-test and cognitive interview stipulated in World Health Organization (WHO) translation guidelines. Content and face validity were conducted as part of the validation process. Content Validity Index (CVI) was done to analyse content validity. Results: The harmonised Malay version of FIES was produced with 1.0 CVI, which was above the 0.8 criteria. Face validity showed good understandability and clarity of FIES. Conclusion: The translated Malay version of FIES had good acceptability, as well as good face validity when tested among the target audience. Thus, a full validation study of the Malay version FIES should be done before it is widely used to measure food insecurity in the population, specifically the Malaysian population.